The Effectiveness Of Ethnomathematics-Based Contextual Teaching And Learning (CTL) On The Mathematical Communication Skills Of Elementary School Students - Rizqi, Hesti Yunitiara; Hawa, Anni Malihatul (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2023)
Students' mathematical communication skills are still low because students do not understand the initial concept. The application of ethnomathematics-based contextual teaching and learning (CTL) to obtain better mathematical communication skills. The purpose of this study was to determine the effectiveness of ethnomathematics-based CTL learning on students' mathematical communication skills. The research method uses quantitative research with a quasy experimental design consisting of 2 classes, namely fifth grade students at SDN 01 Ungaran. The instruments used are in the form of essay questions and observations adapted to indicators of mathematical communication ability. The results showed that the mathematical communication skills of students who were given ethnomathematics-based CTL learning were higher than students who were given mobile learning-based learning, students' mathematical communication abilities increased after being given ethnomathematics-based CTL learning, and there was a positive influence of ethnomathematics-based CTL learning on mathematical communication abilities student. So it was concluded that ethnomathematics-based CTL learning is effective when applied to elementary school students and can facilitate students and teachers in the learning process.